Construct Validation of the Preschool Semantic Comprehension Test (TPSP): Development and Psychometric Evaluation - Taruna, Rexsy; Imanniyah, Anggawati; Dewi, Dina Putri; Salsabila, Hanna; Maizaki, Dwi Cinta Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed to examine the construct validity of the Preschool Semantic Comprehension Test (TPSP) as a measure of semantic comprehension in preschool-aged children. A total of 72 children aged 3–6 years participated and were classified into two groups: typically developing and atypically developing children. Each child completed an individual testing session using TPSP, lasting approximately 10 to 15 minutes. TPSP is a standardized Indonesian assessment tool designed to measure semantic comprehension in preschool-aged children. The test is administered by speech therapists. Data were analyzed using independent samples t-tests, ANCOVA, and effect size estimation (Cohen’s d). Results revealed a highly significant difference in semantic comprehension scores between the two groups (p < .001, d = –2.631). Covariance analysis indicated that this difference remained significant even after controlling for age. These findings support the construct validity of TPSP, demonstrating its sensitivity in distinguishing developmental language profiles. The practical implications highlight TPSP's potential as an effective early assessment tool in Indonesian speech-language therapy settings. Future research is recommended to evaluate TPSP's longitudinal sensitivity and application in multilingual contexts.